Validation of GDPR Compliance in a Library Management System. - Rajačić, Tijana; Boberić-Krstićev, Danijela; Tešendić, Danijela; Milosavljević, Gordana (Information Technology & Libraries, 2025)
This paper explores the challenges of achieving General Data Protection Regulation (GDPR) compliance in library management systems (LMSes) by integrating our novel TeMDA framework into BISIS. BISIS is an LMS used in more than 60 libraries in Serbia. We employed a case study conducted in collaboration between the selected BISIS and TeMDA developers, all authors of this paper. We maintained and presented a detailed development diary to provide insights for other developers seeking GDPR compliance in LMSes. The study provides a practical solution for LMSes to ensure GDPR compliance with minimal effort. The description of the development process, accompanied by listings, tables, and diagrams, can assist LMS developers in determining whether the proposed approach is suitable for them. To the best of our knowledge, this paper presents the first detailed case study on integrating a GDPR compliance framework into an LMS.